(untitled) (Web of Teachers: Inderscience Research, 2024)
This article explores the unique position of states and international organizations as subjects of private international law. Traditionally viewed as actors in public international law, these entities also engage in legal relationships and transactions governed by private international law. Through an analysis of the relevant literature and a review of select case studies, the paper elucidates the evolving role of states and international organizations in the field, addressing questions of immunity, jurisdiction, and the application of national laws.